International validation of the revised European Organisation for Research and Treatment of Cancer Head and Neck Cancer Module, the EORTC QLQ‐HN43: Phase IV. Issue 6 (12th January 2019) - Singer, Susanne; Amdal, Cecilie Delphin; Hammerlid, Eva; Tomaszewska, Iwona M.; Castro Silva, Joaquim; Mehanna, Hisham; Santos, Marcos; Inhestern, Johanna; Brannan, Christine; Yarom, Noam; Fullerton, Amy; Pinto, Monica; et al.
Abstract: Background: We validated the new European Organisation for Research and Treatment of Cancer Quality of Life Head and Neck Module (EORTC QLQ‐HN43). Methods: We enrolled 812 patients with head and neck cancer from 18 countries. Group 1 completed the questionnaire before therapy, and 3 and 6 months later. In group 2 (survivors), we determined test–retest reliability using intraclass correlation coefficients (ICC). Internal consistency was assessed using Cronbach's Alpha, the scale structure with confirmatory factor analysis, and discriminant validity with known‐group comparisons. Results: Cronbach's alpha was >0.70 in 10 of the 12 multi‐item scales. All standardized factor loadings exceeded 0.40. The ICC was >0.70 in all but two scales. Differences in scale scores between known‐groups were >10 points in 17 of the 19 scales. Sensitivity to change was found to be sufficient in 18 scales. Conclusions: Evidence supports the reliability and validity of the EORTC QLQ‐HN43 as a measure of quality of life.